2001
DOI: 10.1002/cta.145
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation behaviour in parallel‐connected boost converters

Abstract: SUMMARYThis paper describes the bifurcation phenomena of a system of parallel-connected d.c.=d.c. boost converters. The results provide important information for the design of stable current sharing in a master-slave conÿguration. Computer simulations and experiments are performed to capture the e ects of variation of some chosen parameters on the qualitative behaviour of the system. In particular, it is found that variation of some parameters leads to Neimark-Sacker bifurcation. Analysis is presented to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…These results are useful for practical design of parallel converter systems to ensure stable period-1 operation in the expected stable region. Similar studies of the parallel converters under the master-slave current sharing scheme have been reported earlier[12]-[13].Fig. 7: Loci of characteristic multipliers as K,,z varies.…”
supporting
confidence: 69%
“…These results are useful for practical design of parallel converter systems to ensure stable period-1 operation in the expected stable region. Similar studies of the parallel converters under the master-slave current sharing scheme have been reported earlier[12]-[13].Fig. 7: Loci of characteristic multipliers as K,,z varies.…”
supporting
confidence: 69%
“…This control signal is then compared with the individual current of the n −1 converters to achieve current sharing. This control method is commonly known as master-slave current-sharing method [25,26], where the voltage source is the master and the current sources are the slaves whose currents are programmed to follow the master's. Our illustrative circuit for the case, as shown in Figure 12(b), is similar to that without a current-sharing loop, except for the control signal of the Norton source converter.…”
Section: With Current-sharing Loopmentioning
confidence: 99%
“…Recently, studies of the dynamical behavior of switching power converter circuits have revealed the possibilities of various kinds of bifurcation behavior, e.g., in pulsewidth-modulated (PWM) dc-dc converters [7]- [12], current-mode controlled dc-dc converters [13]- [15], thyristor and diode circuits [16], [17], free-running dc-dc converters [18], parallel-connected dc-dc converters [19], [20], general switching circuits [21], [22], etc. For the boost PFC preregulators operating in continuous conduction mode (CCM), it has been found that both fast-scale and slow-scale instabilities are possible [23]- [25].…”
Section: Introductionmentioning
confidence: 99%